Expression Of Toll-Like Receptor9 (Tlr9) In Zebra Fish (Danio Rerio) Experimentally Exposed To Aeromonas Hydrophila - A.UMA,; G.REBECCA,; K.SARAVANABAVA, (International Journal of Pharma and Bio Sciences, 2012)
Fishes inhabit the microbe-rich aquatic environment, hence are constantly under the threat of being infected with the microbial pathogens. Non-specific immune system of fish forms the first line of defense in protecting them from the invading pathogens. Toll-like receptors (TLRs) are important components of non-specific immunity that play an essential role in the recognition of the pathogens based on pathogen associated molecular patterns (PAMPs) and in inducing the non-specific immunity. TLR9 recognizes the unmethylated CpG DNA of bacteria and viruses. As the expression level of TLRs in a host is an indicator of its health status and its ability to defend the pathogen challenge, the aim of this study was to compare the tissue-specific expression profiles of TLR9 mRNA in Danio rerio (zebra fish) that were healthy and experimentally exposed to Aeromonas hydrophila, a gram-negative bacterium as it has not been reported so far. Observations of the study shows that tissue-specific differential expression of TLR9 mRNA is present in skin, gill, brain, liver, intestine and kidney of zebra fish and it could be up-regulated upon exposure (4 h) to Aeromonas hydrophila.